From Harm to Healing: Building the Future of ABA with Autistic Voices - Joy F. Johnson (Societies)
Since the 1960s, ABA has been applied to individuals with developmental and behavioral differences, including those later recognized as Autistic. While ABA is grounded in behavioral science, its historical application has raised significant ethical concerns. Early implementations often prioritized enforcing neurotypical conformity over the autonomy and well-being of Autistic individuals, contributing to psychological harm, the development of masking behaviors, and a disregard for neurodivergent needs. These concerns were further exacerbated by the exclusion of Autistic voices in defining intervention goals and measuring outcomes. This paper examines the historical context of ABA, critiques raised by the #ABAisAbuse movement, and the role of social media in amplifying both awareness and misconceptions about behavioral interventions for Autistic individuals. It highlights the challenges posed by self-diagnosis, the limitations of current therapeutic options, and systemic inequities in access to care. A critical analysis underscores the need for standardized, neurodivergent-affirming, and assent-based practices that prioritize the autonomy and individuality of Autistic people. The findings emphasize the necessity of reforming ABA through collaboration with the Autistic community, ensuring their involvement in shaping governance, intervention design, and ethical standards. By addressing historical harms and embedding neurodivergent-affirming principles, ABA can evolve into a practice that supports authentic engagement and fosters trust within the Autistic community. This transformation is not only a professional responsibility but an ethical imperative to align interventions for Autistic individuals with principles of dignity, equity, and inclusion.